2015
DOI: 10.1016/j.drugalcdep.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial sweeteners on breath alcohol concentrations in male and female social drinkers

Abstract: Background Alcohol is often mixed with various nonalcoholic beverages. While consumption of food with alcohol will decrease peak breath alcohol concentrations (BrAC), recent evidence has suggested that mixing alcohol with diet beverages can result in higher BrAC when compared with mixing the same amount of alcohol with sweetened beverages. The purpose of this study was to examine this phenomenon using two different moderate alcohol doses. Methods Twenty participants (10 males) attended five sessions where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Delayed gastric emptying increases the time of exposure of alcohol to gastric alcohol dehydrogenase enzymes, increasing first pass metabolism of alcohol, leading to a lesser absorption and thus a lower BrAC. Previous studies already exposed higher BrAC in humans after drinking alcohol mixed with artificially sweetened (i.e., diet) compared to sugarsweetened (i.e., regular) soft drinks (Wu et al, 2006;Marczinski and Stamates, 2013;Stamates et al, 2015). Sugars in sweet drink reduces the gastric emptying rate (Kalant, 1971) explaining the lower BrAC after drinking V+S compared to V observed in the present study.…”
Section: Alcohol Metabolism and Bracsupporting
confidence: 54%
“…Delayed gastric emptying increases the time of exposure of alcohol to gastric alcohol dehydrogenase enzymes, increasing first pass metabolism of alcohol, leading to a lesser absorption and thus a lower BrAC. Previous studies already exposed higher BrAC in humans after drinking alcohol mixed with artificially sweetened (i.e., diet) compared to sugarsweetened (i.e., regular) soft drinks (Wu et al, 2006;Marczinski and Stamates, 2013;Stamates et al, 2015). Sugars in sweet drink reduces the gastric emptying rate (Kalant, 1971) explaining the lower BrAC after drinking V+S compared to V observed in the present study.…”
Section: Alcohol Metabolism and Bracsupporting
confidence: 54%
“…This lowered BrAC was expected given that the alcohol is less concentrated in this beverage and this outcome has been observed in other research (Peacock et al., ). In addition, it is known that high calorie content soft drink mixers can lower BrAC when compared to lower calorie mixers (Marczinski and Stamates, ; Stamates et al., ). In this study, drinks were consumed on an empty stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Such educational materials could include information about the effect that diet mixers can have on one’s intoxication and that despite the fact that greater objective intoxication may be achieved, one’s subjective intoxication may not be any different (Irwin et al, 2014; Marczinski & Stamates, 2013). Also, experimental evidence (Marczinski & Stamates, 2013; Stamates et al, 2015) suggests that up to a 25% difference in greater BrACs may be observed when consuming alcohol with diet beverages. Standard drink calculators may need to be adapted so drinkers can more effectively estimate their BAC.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing alcohol with artificial sweeteners (i.e., diet beverages) has been linked to greater objective levels of intoxication, such as higher breath alcohol concentrations (BrACs; Irwin, Shum, Desbrow, & Leveritt, 2014; Marczinski & Stamates, 2013; Stamates, Maloney, & Marczinski, 2015) and blood alcohol concentrations (BACs; Wu, Chaikomin, Doran, Horowitz, & Rayner, 2006). This may be because diet mixers facilitate faster alcohol absorption rates (see Marczinski & Stamates, 2013 for discussion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation